2000
DOI: 10.1002/1097-0223(200009)20:9<705::aid-pd904>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

How women deal with the results of serum screening for Down syndrome in the second trimester of pregnancy

Abstract: To gain insight into how pregnant women experience serum screening for Down syndrome, we sent questionnaires to two groups of relevant subjects in the north of the Netherlands. The questionnaires addressed the following issues: decision‐making process, knowledge and opinions. Questionnaire A was sent to women of 36 years of age and older (n=99) (group A) who were all 20 to 36 weeks pregnant at that time. In the Netherlands prenatal diagnosis is routinely available to these women. Questionnaire B was sent to wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 11 publications
3
43
1
1
Order By: Relevance
“…73 The two most commonly used validated measures of anxiety in applied health settings are the Hospital Anxiety and Depression Scale (HADS) 69 and the State-Trait Anxiety Inventory (STAI). 67,74 Twenty-four studies within the review measured anxiety, 12 employed the STAI, 12,17,[43][44][45]47,48,[75][76][77][78][79] one the STAI and HADS, 49 three used an unvalidated questionnaire measure 60,64,65 and ten ascertained anxiety levels by interview. 55,59,[80][81][82][83][84][85] Of these studies, nine assessed anxiety before women were tested 12,17,[43][44][45]47,48,76,77 and the rest after testing and/or after test results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…73 The two most commonly used validated measures of anxiety in applied health settings are the Hospital Anxiety and Depression Scale (HADS) 69 and the State-Trait Anxiety Inventory (STAI). 67,74 Twenty-four studies within the review measured anxiety, 12 employed the STAI, 12,17,[43][44][45]47,48,[75][76][77][78][79] one the STAI and HADS, 49 three used an unvalidated questionnaire measure 60,64,65 and ten ascertained anxiety levels by interview. 55,59,[80][81][82][83][84][85] Of these studies, nine assessed anxiety before women were tested 12,17,[43][44][45]47,48,76,77 and the rest after testing and/or after test results.…”
Section: Discussionmentioning
confidence: 99%
“…55,59,[80][81][82][83][84][85] Of these studies, nine assessed anxiety before women were tested 12,17,[43][44][45]47,48,76,77 and the rest after testing and/or after test results. Most studies were carried out in the UK, 12,17,[43][44][45]48,59,65,83,84 five in North America, 47,74,78,79,85 three in Finland, 55,80,82 two in The Netherlands 60,64 and one each in Denmark 81 and Italy. 77 As all studies in this chapter employing a validated measure of anxiety used the STAI, the STAI is discussed in more detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was based on a questionnaire used in a previous study (Weinans et al, 2000). Data were analyzed by the Statistical Package for Social Sciences (SPSS/Windows).…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have found that many women continue to experience residual anxiety following a problematic screening result, even when diagnostic testing showed a 'normal' result (e.g., Baillie, Smith, Hewison, & Mason, 2000;Tymstra, 1986;Weinans et al, 2000). However, what is clear is that in the UK, with its recent policy move towards the routine offer of screening for fetal anomalies, particularly Down's syndrome, and the potential move to first trimester screening, with its generally higher uptake rate, many more women will be confronting these ethical dilemmas.…”
Section: Ultrasound Scans In First Trimester Screeningmentioning
confidence: 99%